End the lockdown? Why restrictions are being lifted too fast for some and not fast enough for others; Raus aus dem Lockdown? Warum es manchen zu schnell und anderen nicht schnell genug geht - Claudia Diehl; Felix Wolter (University of Konstanz, Cluster of Excellence "The Politics of Inequality", Das Progressive Zentrum e.V., 2020)
Trust matters more than self-interest: That is the result of an online survey we conducted among roughly 4,800 participants in April and May 2020. Individual attitudes towards easing restrictions to contain the coronavirus pandemic are not primarily shaped by whether people fear economic or family-related consequences for themselves or for society. Rather, it is perceived infringements on basic rights that motivate respondents to demand that restrictions be lifted. Respondents from East Germany and those who tend not to trust public institutions in the first place are especially critical of the containment measures. The discussion about easing restrictions, therefore, is not so much about the varying degrees to which individuals are affected, but rather about the degree of trust in public institutions generally. – – Vertrauen ist wichtiger als Eigeninteresse: Das zeigt eine OnlineBefragung, die wir von April bis Mai 2020 unter knapp 4800 Teilnehmenden durchgeführt haben. Die Haltung zur Lockerung pandemiebedingter Beschränkungen wird weniger dadurch bestimmt, ob jemand daraus wirtschaftliche oder familiäre Folgen für sich selbst oder die Gesellschaft befürchtet. Vielmehr bringen wahrgenommene Grundrechtseinschränkungen die Befragten dazu, Lockerungen zu fordern. Befragte aus dem Osten Deutschlands und solche, die ohnehin ein geringes Vertrauen in staatliche Institutionen haben, sehen die Eindämmungsmaßnahmen besonders kritisch. Bei der Lockerungsdiskussion geht es also weniger um unterschiedlich starke individuelle Betroffenheit als um das Vertrauen in staatliche Institutionen.
urn:nbn:de:bsz:352-2-d6dbbo7u8khf7
Keywords: 320